Silencing of a Pseudo-nitzschia arenysensis lipoxygenase transcript leads to reduced oxylipin production and impaired growth - Sabatino, Valeria (The New phytologist, 2022)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.